DAMPAK OLAHRAGA PADEL TERHADAP GAYA HIDUP SEHAT DI KALANGAN DEWASA MUDA - Risa Agus Teguh Wibowo; Slamet Sudarsono; Cristian Batistuta; Rakan Raditya Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Padel is a rapidly growing racket sport in Indonesia and has become part of the lifestyle of young adults. This study aimed to analyze the influence of padel on healthy lifestyles among young adults aged 20–35 years in Solo City. A mixed-method approach with an explanatory sequential design was employed. A total of 100 participants completed a healthy lifestyle questionnaire for the quantitative phase, while 10 participants were selected for in-depth interviews to explore their experiences and motivations for playing padel. Quantitative data were analyzed using descriptive statistics and Pearson correlation, whereas qualitative data were examined through thematic analysis. The findings revealed that respondents demonstrated a high level of healthy lifestyle, with an overall mean score of 4.22 ± 0.46. The frequency of playing padel was positively and significantly associated with physical activity (r = 0.71; p < 0.001), stress management (r = 0.64; p = 0.001), sleep quality (r = 0.59; p = 0.002), and overall healthy lifestyle scores (r = 0.73; p < 0.001). Qualitative findings generated four major themes: increased exercise motivation, reduced stress, enhanced social interaction, and the development of healthier lifestyle behaviors. The integration of quantitative and qualitative findings indicates that padel contributes not only to increased physical activity but also to psychological and social well-being, supporting the adoption of healthier lifestyles among young adults. Therefore, padel has strong potential as a community-based physical activity to support public health promotion programs.